Intrarenal Distributions and Changes of Angiotensin-Converting Enzyme and Angiotensin-Converting Enzyme 2 in Feline and Canine Chronic Kidney Disease - MITANI, Sawane (The Japanese Society of Veterinary Science, 2013)
Angiotensin-converting enzyme (ACE) is a key enzyme in the renin-angiotensin system (RAS). ACE2 is a newly identified member of the RAS. The present immunohistochemical study focused on changes in intrarenal ACE and ACE2 immunoreactivity in feline and canine chronic kidney disease (CKD). ACE immunoreactivity was predominantly observed in the brush border of the proximal tubules in dogs and cats. ACE immunoreactivity was lower in CKD kidneys than in normal kidneys, and quantitative analysis demonstrated negative correlations between ACE and renal tissue damage in dogs. ACE2 immunoreactivity was also detected in the proximal tubules; it increased or decreased with CKD in dogs, depending on the renal region assessed. The changes in ACE and ACE2 in CKD were associated with the plasma creatinine concentration in dogs. Findings from dogs with glomerulonephritis were similar to those from dogs with non-glomerulonephritis. The present study suggests that changes in the intrarenal expression of ACE and ACE2 contribute to the pathological mechanisms of canine CKD, but not to the mechanisms of feline CKD.